Development of Maritime Research in the Digital Era Bibliometric Analysis - Yusup, Muhammad Firdaus Bin; Syaifullah, Muhammad (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
This study aims to analyze the development of maritime research in the digital era through a bibliometric approach, with a particular focus on scientific publications in the period 2015-2024. The methodology used includes data collection from two major academic databases, namely Scopus and Web of Science, selected for their comprehensive coverage and availability of metadata. The data collection process included the use of a systematic search string with keywords such as